Pemahaman dan Partisipasi Guru Sekolah Dasar Dalam Menulis Karya Ilmiah - Maulina Hendrik; Vika Martahayu (Society, 2018)
The general objective of the study is to identify the understanding and participation of teacher in academic writing.The specific objectives of the study are to (i) identify the understanding of elementary school teacher in academic writing in Rangkui District; (ii) to identify the participation of elementary school teacher in academic writing in Rangkui District; and (iii) to examine factors that affect the elementary school teacher in academic writing in Rangkui District. The study employed the qualitative approach with source of data as follows: (i) 50 elementary school teachers as the primary data; and (ii) documentation derived from some literatures and other reading sources as the secondary data. The data was gained by using the interview and documentation. Furthermore, it was analyzed by using data analysis technique i.e. data reduction, data presentation, decision making. The results showed: (i) 28 % of respondents considered as having understanding, 35 % of them considered as lack of understanding, and 37 % considered as not having understanding at all in academic writing. (ii) in terms of the participation level of elementary school teacher, 20 % of respondents stated often, 35 % of them stated rarely, and 45 % of them stated not having the academic writing. (iii) Factors that affect teacher in participating on having the academic writing were lack of time, motivation, knowledge and idea.